Pengaruh Kualitas Produk, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian pada PT Graha Informatika Nusantara Sumatera Utara - Katika Adelia; Rosnaida Rosnaida (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The background of this research is based on the increasing level of business competition in the information technology sector, which requires companies to maintain customer satisfaction through high-quality products, competitive pricing, and excellent service. This study was conducted to examine the influence of product quality, price, and service quality on purchasing decisions at PT Graha Informatika Nusantara. The objective of this study was to determine both partially and simultaneously the effect of product quality, price, and service quality on purchasing decisions. This research employed a quantitative approach with an associative research method. The population consisted of customers of PT Graha Informatika Nusantara North Sumatra, and the sample size of 96 respondents was determined using the Cochran formula. The sampling technique applied was incidental sampling. Research data were collected through the distribution of Likert-scale questionnaires. The collected data were processed using SPSS version 27 and analyzed through multiple linear regression analysis. The results of the study indicated that product quality, price, and service quality had a positive and significant effect on purchasing decisions, both partially and simultaneously. These findings suggest that improving these factors can increase customer purchasing decisions and strengthen the company’s competitiveness.